2005
DOI: 10.1016/j.bcp.2005.09.021
|View full text |Cite
|
Sign up to set email alerts
|

Role of elevated S-adenosylhomocysteine in rat hepatocyte apoptosis: Protection by betaine

Abstract: Previous studies from our laboratory have shown that ethanol consumption results in an increase in hepatocellular S-adenosylhomocysteine levels. Because S-adenosylhomocysteine is a potent inhibitor of methylation reactions, we propose that increased intracellular S-adenosylhomocysteine levels could be a major contributor to ethanol-induced pathologies. To test this hypothesis, hepatocytes isolated from rat livers were grown on collagen-coated plates in Williams' medium E containing 5% FCS and exposed to varyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
78
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(82 citation statements)
references
References 57 publications
2
78
0
Order By: Relevance
“…Recent studies from several groups, including ours, documented that chronic alcohol consumption not only caused a decrease in hepatic SAM levels, but also an elevation in SAH levels, leading to a markedly decreased SAM/SAH ratio, an indicator of abnormal transmethylation status. [13][14][15] Furthermore, we showed that accumulation of SAH in the liver sensitized to tumor necrosis factor ␣ (TNF-␣)-induced hepatotoxicity. 14 It is now well accepted that adipose tissue is a much more active tissue than originally thought and that it plays a critical role in the regulation of energy homeostasis and inflammatory reactions in other tissues, including liver and skeletal muscle.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies from several groups, including ours, documented that chronic alcohol consumption not only caused a decrease in hepatic SAM levels, but also an elevation in SAH levels, leading to a markedly decreased SAM/SAH ratio, an indicator of abnormal transmethylation status. [13][14][15] Furthermore, we showed that accumulation of SAH in the liver sensitized to tumor necrosis factor ␣ (TNF-␣)-induced hepatotoxicity. 14 It is now well accepted that adipose tissue is a much more active tissue than originally thought and that it plays a critical role in the regulation of energy homeostasis and inflammatory reactions in other tissues, including liver and skeletal muscle.…”
mentioning
confidence: 99%
“…These alterations are thought to be involved in the pathogenesis of ALD. [10][11][12][13][14][15] Ji and Kaplowitz 12 reported increased hepatic homocysteine accumulation in an intragastric alcohol infusion animal model of ALD and postulated that hyperhomocysteinemia-induced endoplasmic reticulum stress might be implicated in hepatocyte death in alcohol-fed mice. Recent studies from several groups, including ours, documented that chronic alcohol consumption not only caused a decrease in hepatic SAM levels, but also an elevation in SAH levels, leading to a markedly decreased SAM/SAH ratio, an indicator of abnormal transmethylation status.…”
mentioning
confidence: 99%
“…It is also a metabolite of choline and an essential biochemical component of the methionine-homocysteine cycle (8). Hepatoprotective effects of betaine were reported in a variety of experimental animal models of liver diseases, including alcoholic liver disease and bile acid-induced liver injury (4,11,15,18), with different mechanisms involved. The therapeutic effects of betaine on NAFLD have also been investigated and reported in both clinical and experimental studies (1,17,21,24,28).…”
mentioning
confidence: 99%
“…In addition, betaine homocysteine methyltransferase (BHMT) is an enzyme responsible for remethylation of homocysteines to form methionine. Suppression of this enzyme can result in increased generation of homocysteine and an increased activity of antioxidant enzymes (Kharbanda et al, 2005;Moat et al, 2000). In a previous study, De Wit et al (2008) found that BHMT was down-regulated in the liver of zebrafish after TBBPA exposure, and concluded that this was a result of oxidative stress.…”
Section: Discussionmentioning
confidence: 99%